Monitoring of organic micropollutant behavior and fate in a full-scale conventional biological urban wastewater treatment plant - Demirbilek, D.; Ipek, U.; Yetis, U. (Springer, 2025)
Organic micropollutants, found at trace levels in nature, are causing significant concern due to their toxic, carcinogenic, and mutagenic effects. In this study, the fate and removal of organic micropollutants were monitored covering all seasons in an urban wastewater treatment plant in Turkey. The plant influent, effluent, and aeration basin were sampled seven times in the years of 2019-2020; and three surfactants (linear alkylbenzene sulfonate, nonylphenol mono-di-ethoxylate, nonylphenol), polychlorinated biphenyls and polyaromatic hydrocarbons were monitored in this context. The plant was being operated in the endogenous respiration phase during the monitoring period without sludge removal. Results obtained showed that the highest NH3-N removal (41%) of the study period was realized in March when the lowest mixed liquid volatile suspended solids value (380 mg/L) and the lowest sludge age were observed. In this month, the highest organic micropollutants removal efficiency was obtained in relation to the increased metabolic activity. On the other hand, in August, when the highest mixed liquid volatile suspended solids value (1,750 mg/L) was observed, the lowest organic micropollutants removal was recorded, with the lowest NH3-N removal (6%). The removal of linear alkylbenzene sulfonate and nonylphenol mono-di-ethoxylate was high during the period, and microorganisms could metabolize these pollutants efficiently. Polychlorinated biphenyls, polyaromatic hydrocarbons, and nonylphenol were resistant to metabolic degradation, so they were present in high amounts at various stages of the treatment process. Due to the poor plant treatment performance, a high quantity of organic micropollutants was discharged into the receiving environment.
Keywords: Activated sludge; Organic micropollutants; Seasonal monitoring; Urban wastewater treatment